Fragilidade em idosos: análise conceitual. - Andrade, Ankilma do Nascimento (2010)
Introduction: In recent decades, it is observed an increase in scientific production on frailty in the elderly. Nevertheless, there is no consensus on the definition and use of that concept. Thus, in view of the need to clarify, and so as to facilitate its practical applicability, the study was conducted. Objective: To analyze the concept frailty in elderly people, identifying the possible factors antecedents, critical attributes and consequences of the phenomenon. Methodology: The study was guided by the conceptual model of analysis proposed by Walker and Avant. It was performed by the analysis of a literary corpus composed of fifty papers relevant to the subject, published in Portuguese, English and Spanish, from 2001 to 2009. The operational procedure of this analysis involved a careful and objective reading of selected works, with the identification and clipping of the recording units which included background, attributes and consequences of frailty in the elderly. Results: The results confirmed the background of the concept, psychosocial events, such as increasing age, low income, low education, absence or poor social support, negative self-perception of health status and events of a physical / biological morbidities, low physical activity / inactivity, changes in body weight, cumulative decline in multiple organ systems, inadequate nutritional intake, malnutrition, sensory and cognitive deficits, depression / depressive symptoms and polypharmacy. With regard to the attributes of frailty in elderly people, there were: abnormal gait, slowness and instability, self-reported fatigue / exhaustion, muscle weakness, reduced grip strength and vulnerability to environmental stressors and psychosocial conflicts. With regard to the consequences, these included increased rates of hospitalization and institutionalization, anticipation of death, risk for falls / fall / fear of falling, functional disability / dependency, incontinence and pressure ulcer risk. Conclusion: Based on theoretical analysis of the concept it was elaborated the following the conceptual definition for the phenomenon: frailty in the elderly is a multidimensional e multideterminated event, characterized by vulnerability to stressors by biopsychosocial and environmental changes in the musculoskeletal system, in motor function and body composition, which results in functional impairments and their outcomes.